Production and meat quality of broiler chickens with the use of a probiotic complex of bifidobacteria and lactobacilli - O. M. Iakubchak; A. Y. Vivych; J. V. Hryb; S. Н. Danylenko; T. V. Taran (Regulatory Mechanisms in Biosystems, 2024)
The prohibition of antibacterial agents in animal husbandry has spurred research into the creation and study of new probiotic supplements aimed at normalizing the gut microbiota to ensure colonization resistance of the host organism. This resistance prevents the colonization of the gastrointestinal tract by pathogenic and opportunistic microflora. Scientists from many countries have developed a range of preparations based on the normal gut microbiota, such as lactobacilli and bifidobacteria, which are used to maintain and restore the biocenosis of the digestive tract. These probiotics are also effective therapeutic and preventive agents for poultry digestive tract diseases, helping correct gut microbiocenosis. In our study, we investigated the impact of the combined probiotic preparation "TIMM-P" on the productive characteristics of poultry and the quality and preservation of broiler chicken meat. This study determined clinical indicators, absolute and average daily weight gains, the meat quality of broiler chickens, and its chemical composition under the influence of the probiotic supplement. It was found that administering "TIMM-P" in courses on days 1–5, 21–25, and 30–35 positively influences the growth of muscle tissue in poultry. Determination of the chemical composition of meat in 42-day-old experimental broiler chickens indicated a significant increase in total protein content in the muscle tissue using the probiotic. Additionally, the absolute and average daily weight gains of the broiler chickens in the experimental group significantly increased during days 15–28 and 29–42 of the study. We observed a significant impact of the probiotic preparation on extending the shelf life of poultry meat based on the study of organoleptic and chemical indicators of broiler chicken meat during refrigerated storage. On the 7th and 9th days of storage, the carcasses of the experimental group that received the probiotic showed a significant decrease in pH levels, acid number, and peroxide number of the fat in the meat. Thus, oral administration of the probiotic preparation increases live weight gains, improves meat quality indicators of broiler chickens, and extends its shelf life. The obtained results have important practical significance as they scientifically substantiate the use of probiotic preparation as a means to preserve livestock, increase live weight gains of broiler chickens, and improve poultry meat quality. Therefore, the complex probiotic preparation "TIMM-P" can be recommended for use in broiler chicken farming.